Acompanhamento das ouvidorias do governo do estado de São Paulo - Barros, Heraldo de (2011)
Dissertation elaborated according to the term of reference made by FGV and the Public Management Secretariat of the São Paulo State Government (SGP), whose objective is to analyze and propose improvements to the semiannual report of São Paulo’s 'state ombudsmen'. The semiannual report is a compilation of all the São Paulo's 'state ombudsmen' information, made by SGP. The dissertation analyzes the report and the processes that regard its elaboration. Therefore, it aimed the understanding of: the 'state ombudsmen' institutional role, despite their lack of independence; the types of analysis on it, with quantitative comparisons that doesn't consider different realities; the information flow, from the moment the citizen makes his manifest to the delivery of the report, considering the different channels; IT system underutilized; misinterpretation of the 'ombudsmen' role, informally coordinated by the SGP. After the analysis, improvement suggestions have been made, regarding issues such as: presentation, standards, participation, communication, IT system and governance.